Hubungan penyajian susu formula dengan kejadian diare pada bayi di Puskesmas Pahandut - Martha, Putri Ellya; Arifin, Syamsul; Yuliani, Ni Nyoman (Fakultas Kedokteran Universitas Palangka Raya, 2023)
Diarrhea is a change in consistency that happened suddenly due to the water content in the feces exceeding normal in baby and toddlers with a frequency increase of defecation more than 4 times in 24 hours. Baby formula is a good medium for the growth of bacteria and is also easily contaminated if the presentation does not pay attention to the hygienic aspect. This research used analytic observational method with a cross sectional research approach on 93 respondents of mother who have babies < 12 months and used statistical test chi square with significant level < 0,005. The results of the study found that the occurence diarrhea was dominated by the presentation of unhygienic baby formula (55.6%). The results of the bivariate analysis in this research showed that there was a significant relationship between the method of serving baby formula for diarrhea in the UPT BLUD Puskesmas Pahandut with the results of the chi square statistical test showing that the value of p = 0.009 (p < 0.05). There is a connection between the method of serving baby formula and the occurence of diarrhea in the working area of ​​BLUD UPT Puskesmas Pahandut.